PENGARUH DISIPLIN KERJA DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA CV MANDIRI SUPERMARKET GROUP MEDAN - tommy king; Yulinda yulinda (Jurnal Media Informasi Manajemen, 2013)
In any organization, the human is one very important component. How perfect an organization in planning, policy, technology owned by an organization can not run smoothly if not supported by reliable labor. With qualified human resources, organizations are able to manage employees effectively and efficiently and be able to support the achievement of organizational research was conducted at CV Mandiri Supermarket Group Medan. This study uses Work Discipline,and Motivation as independent variables and employee performance as the dependent variable. The purpose of this study was to analyze the influence of Work-discipline and motivation to work on Employee Performance. The samples used were employees of CV Mandiri Supermarket Group Medan where the number of samples determined in this study as many as 52 respondents. The analysis used include test validity, test reliability, test classic assumptions, test the multiple linear regression, hypothesis testing and the coefficient of determination (R2). Based on the F-test is performed and the results of multiple linear regression analysis above can be seen that the simultaneous work discipline and motivation to work have a positive and significant impact on performance, Based on the results of t tests, proved that partial  Work Disciplne does not affect and no significant effect on performance, while motivation has positive and significant impact on performance. Keyword : Work Discipline, Motivation, and Employee Performance